Internações por condições cardiovasculares sensíveis à atenção primária e a relação com a Estratégia Saúde da Família em municípios de médio porte do Paraná, Brasil, 2008 a 2017 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Conditions Sensitive to Primary Health Care (CSAPS) are a set of health problems whose risk of hospitalizations could be reduced by an effective action at the primary level. Cardiovascular diseases are among the main causes of these hospitalizations. Objectives: To analyze Hospitalizations for Cardiovascular Conditions Sensitive to Primary Health Care (ICCSAP) in medium-sized municipalities in the state of Paraná and the relationship with the coverage of the Family Health Strategy (ESF), between 2008 and 2017.Method: Ecological study, of temporal trend. The causes of the hospitalizations analyzed were systemic arterial hypertension, angina, congestive heart failure and cerebrovascular diseases, according to the Brazilian list of conditions sensitive to primary care. All hospitalizations that occurred in the Unified Health System, of residents aged 40 to 74 years, in medium-sized municipalities in the state of Paraná, made available by DATASUS, in the Tabwin program, were analyzed. The data referring to the resident population were also obtained by consulting DATASUS. Annual hospitalization rates were calculated according to the variables cause, sex, age and municipality of residence, per 10,000 inhabitants. The percentage of the population covered by the ESF of the municipalities was obtained from the Support Room for Strategic Management, available on the Ministry of Health website. The data analysis included the polynomial regression for hospitalization rate trends, the percentage variation for coverage by the ESF, and Pearson and Spearman's linear correlation coefficients for the correlation between coverage by the ESF and the ICCSAP rates. The level of significance was set at p <0.05. Results: Considering all the municipalities together, there was a decreasing trend for the total of ICCSAP rates, for men and women and for the age groups of 40 to 59 years and 60 to 74 years (all p <0.001). Higher rates were observed for the 60 to 74 age group and for the male gender, in all years. Considering each cardiovascular disease, there was a decreasing trend in rates for SAH (p <0.001), congestive heart failure (p <0.001), and cerebrovascular diseases (p <0.01), even when stratified by sex and age group. The rates for angina showed an increasing trend (p <0.001), even when stratified by sex and age group. There was a decreasing trend in the rates of ICCSAP in nine of the 16 municipalities studied (56.2%), the others with an increasing trend. The municipalities together and five of them showed an inverse correlation between the ESF coverage and the ICCSAP rates. Conclusion: The results suggest a reduction in HACSC rates, except for angina. The correlation between ESF coverage and ICCSAP rates must be analyzed considering local specificities. The importance of ICCSAP is highlighted as an indicator in the monitoring of cardiovascular diseases.
Keywords: Atenção Primária à Saúde; Indicadores de Qualidade em Assistência à Saúde; Hospitalização; Assistência à Saúde; Doença Crônica; Primary Health Care; Health Care Quality Indicators; Hospitalization; Delivery Health Care; Chronic Disease; CNPQ::CIENCIAS DA SAUDE